1
$\begingroup$

I want to estimate $n+m$ parameters with the equation: $$\hat\theta=\left[\frac{1}{N}\sum_{t=1}^N \varphi(t)\varphi^T(t)\right]^{-1}\left[\frac{1}{N}\sum_{t=1}^N\varphi(t)y(t)\right]$$ where $\varphi$ is a vector of regressors and $\theta$ the vector of parameters. Then my book derive an expression for the estimation error: $$\hat\theta-\theta_0 =\left[\frac{1}{N}\sum_{t=1}^N\varphi(t)\varphi^T(t)\right]^{-1} \left[\frac{1}{N}\sum_{t=1}^N\varphi(t)y(t)-\left\{\frac{1}{N}\sum_{t=1}^N\varphi(t)\varphi^T(t)\right\}\theta_0\right]$$ this makes no sense to me! Why the term in curly braces? And why inside the second factor? Please help.

$\endgroup$
  • $\begingroup$ whoa... I guess I really have some sort of phobia for big formulae. Thanks! $\endgroup$ – gurghet Jun 18 '11 at 18:11
  • $\begingroup$ @Bogdan, please convert your comment to answer. $\endgroup$ – mpiktas Jun 20 '11 at 6:57
1
$\begingroup$

Let $A=\frac{1}{N}\sum_{t=1}^N \varphi(t)\varphi^T(t)$ and $B=\frac{1}{N}\sum_{t=1}^N\varphi(t)y(t)$
Then by distributivity $A^{-1}[B-A\theta_0]=A^{-1}B-A^{-1}A\theta_0=\hat{\theta}-\theta_0$.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.